Penguatan Kapasitas Pengelolaan Media Sosial Untuk Promosi Produk UMKM Kota Cirebon - Saeful Anwar; Fathurrohman; Aulia Adisty Hervianne; Indah Nur Hasanah (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in economic growth, employment generation, and community welfare. However, the use of social media as a promotional tool among MSMEs in Cirebon City remains limited due to insufficient digital literacy, low-quality promotional content, and the absence of structured social media management strategies. This community service program aimed to strengthen the capacity of MSME owners in managing social media for product promotion through practice-based training and mentoring. The implementation consisted of needs assessment, training, hands-on practice, mentoring, monitoring, and evaluation. Training materials included digital branding, promotional content creation, product photography, caption writing, content calendar development, and the optimization of Instagram, Facebook, TikTok, and WhatsApp Business. The results demonstrated significant improvements in participants' ability to manage business social media accounts, produce more engaging promotional content, organize structured publishing strategies, and enhance customer engagement. The program also produced practical outputs, including professionally managed social media accounts, content calendars, and a simple social media management guide. These findings indicate that combining training with continuous mentoring is effective in improving digital competencies and strengthening the competitiveness of MSMEs.